Distinct growth stages controlled by the interplay of deterministic and stochastic processes in functional anammox biofilms. (15th July 2021) - Niederdorfer, Robert; Fragner, Lisa; Yuan, Ling; Hausherr, Damian; Wei, Jing; Magyar, Paul; Joss, Adriano; Lehmann, Moritz F.; Ju, Feng; Bürgmann, Helmut
Highlight: Succession of functional anammox biofilms under mainstream conditions. Distinct biofilm growth stages emerge in terms of structure and community composition. Growth stages are a prerequisite for community structure, stability and function. Importance of stochastic and deterministic processes shift during biofilm assembly. Abstract: Mainstream anaerobic ammonium oxidation (anammox) represents one of the most promising energy-efficient mechanisms of fixed nitrogen elimination from wastewaters. However, little is known about the exact processes and drivers of microbial community assembly within the complex microbial biofilms that support anammox in engineered ecosystems. Here, we followed anammox biofilm development on fresh carriers in an established 8m 3 mainstream anammox reactor that is exposed to seasonal temperature changes (~25-12°C) and varying NH4 + concentrations (5-25 mg/L). We use fluorescence in situ hybridization and 16S rRNA gene sequencing to show that three distinct stages of biofilm development emerge naturally from microbial community composition and biofilm structure. Neutral modelling and network analysis are employed to elucidate the relative importance of stochastic versus deterministic processes and synergistic and antagonistic interactions in the biofilms during their development. We find that the different phases are characterized by a dynamic succession and an interplay of both stochastic and deterministic processes. The observed growth stages ( Colonization, Succession and Maturation ) appear to be the prerequisite for the anticipated growth of anammox bacteria and for reaching a biofilm community structure that supports the desired metabolic and functional capacities observed for biofilm carriers already present in the system (~100gNH4-N m 3 d −1 ). We discuss the relevance of this improved understanding of anammox-community ecology and biofilm development in the context of its practical application in the start-up, configuration, and optimization of anammox biofilm reactors. Graphical abstract: Image, graphical abstract